Effect of Using Chlorhexidine Solution on Occurrence of Ventilator -Associated Pneumonia among Critical Care Unit Patients (Journal of Hama University, 2022)
mechanical ventilation is a basic treatment capable of saving the lives of patients with critical conditions and respiratory failure, but these patients are vulnerable to the development of complications. so that infection control is the responsibility of all health care elements, especially the nursing staff. Knowing the effect of using chlorhexidine solution on the occurrence of ventilator-associated pneumonia among Critical Care Unit Patients. A quasi-experimental study was conducted on all intubated patients who fulfilled the selection criteria in the intensive care unit, where they numbered 30 patients in Tishreen University Hospital in Lattakia. Data were collected using two tools, the first is a demographic, clinical and health data collection form, and the second is the Pneumonia Evaluation Scale (CPIS) according to Nasiriani et al., (2016). The results showed that there is differences with a statistical significance in the CPIS score between the two study groups on the fifth day (P = 0.014). The results showed that there was differences with a statistical significance of the in the length of stay in the hospital due to the average value of CPIS in the experimental (P = 0.024) and the control groups (P = 0.001), and it also showed a strong and statistically significant positive correlation between the length of stay in the hospital and the incidence of Ventilator -Associated Pneumonia (VAP). The study recommended using of chlorhexidine solution as a mouthwash in patients placed on a mechanical ventilator, Conducting more similar studies with an increase in the number of participating patients to include several hospitals in the governorate, Develop a- protocol based on modern scientific evidence for oral care to be applied in the intensive care unit, Subjecting the nursing staff in the intensive care unit to educational training courses on comprehensive oral care.